Computerized welding process selection and parameter determination - A. Aregia, Tarek Abdelhadi (2010)
Welding is a materials joining process in which two or more parts are coalesced at their contacting surfaces by a suitable application of heat and/or pressure. In today technology, welding is an important process in manufacture and assembly project. There is a need for welding expertise to get the best welding qualities. For small and medium industry, employing a welding expert is quite costly. The purpose of this study is to design and develop an expert system to select suitable welding process and determining the optimum welding parameters. While conducting this project, the important question that the project focused on was how an effective and efficient computerized system can help in selecting the welding process and determine process selection parameters. Also an exclusive research was done to collect data about the arc and other welding processes parameters, designing database for the welding processes, welding parameters, and work-pieces characteristics related to the parameters of welding process, and also an algorithms was developed to find out the most suitable welding process and its parameters related to a specific work-piece. So having an expert system that helps in selecting the suitable welding process and determine process parameters can help industries and welders to set the welding process time, less expensive and extensive clerical work, and provide reliable and consistent welding processes. However, the required methodology for this project development began from initial planning, an analysis, design, development of a prototype, and finally implementation and application testing of the system was executed. Farther more, evolutionary prototype is chosen as the system development methodology for this project. On the other hand, a prototype of the proposed system was developed and deployed by using Oracle Application Express version 3.2 as a web page developer tool and Oracle Database 11g as data storage application. Finally, this project is developed to achieve the objective of improving the welding processes selections by using expert system, which is a computer program with reasoning capabilities to solve a particular problem.